Integrating Scientific Approaches in Digital Learning Materials to Improve Spatial Abilities in Cube Geometry: A Research and Development - Guci, Putri Tipakaden; Siregar, Budi Halomoan (PT Inovasi Pratama Internasional, 2024)
This research aims to determine the level of validity, practicality and effectiveness of digital teaching materials based on a scientific approach, so that they can improve students' spatial abilities in cube material. This type of research is development research with the ADDIE development model. Research instruments in the research include questionnaire validation sheets, lesson plan validation sheets, digital teaching material validation sheets, test instrument validation sheets, spatial ability tests, as well as teacher and student response questionnaires to digital teaching materials. The research results show that: (1) the scientific approach-based digital teaching materials developed have met the validity criteria based on validator assessments with the average validity of digital teaching materials for material being 3.44 and 3.82 for media in the very appropriate category; (2) the scientific approach-based digital teaching materials developed have met the practicality criteria through: a) the results of the student response questionnaire to digital teaching materials show a practicality percentage of 82.75% in the very practical category, b) the results of the teacher response questionnaire to digital teaching materials show practicality percentage 91.67% in the very practical category; (3) The scientific approach-based digital teaching materials developed meet the effective criteria with: a) classical student learning completeness of 90%, b) more than 65% of students have achieved 75% of the learning objectives for each indicator, c) increasing students' spatial abilities After using digital teaching materials, it can be seen from the students' average score increasing from 47.67 in the pretest to 86.50 in the posttest. The results of the N-Gain analysis which shows that students' spatial abilities have increased by 0.725, meaning they are in the high category.